On the Effect of Soft Molecularly Imprinted Nanoparticles Receptors Combined to Nanoplasmonic Probes for Biomedical Applications - Cennamo, Nunzio; Bossi, Alessandra Maria; Arcadio, Francesco; Maniglio, Devid; Zeni, Luigi (Frontiers in Bioengineering and Biotechnology, 2021)
Soft, deformable, molecularly imprinted nanoparticles (nanoMIPs) were combined to nano-plasmonic sensor chips realized on poly(methyl methacrylate) (PMMA) substrates to develop highly sensitive bio/chemical sensors. NanoMIPs (dmean < 50 nm), which are tailor-made nanoreceptors prepared by a template assisted synthesis, were made selective to bind Bovine Serum Albumin (BSA) and were herein used to functionalize gold optical nanostructures placed on a PMMA substrate, this latter acting as a slab waveguide. We compared nanoMIP-functionalized non-optimized gold nanogratings based on periodic nano-stripes to optimized nanogratings with a deposited ultra-thin MIP layer (< 100 nm). The sensors performances were tested by the detection of BSA using the same setup, in which both chips were considered as slab waveguides, with the periodic nano-stripes allocated in a longitudinal orientation with respect to the direction of the input light. Result demonstrated the nanoMIP-non optimized nanogratings showed superior performance with respect to the ultra-thin MIP-optimized nanogratings. The peculiar deformable character of the nano-MIPs enabled to significantly enhance the limit of detection (LOD) of the plasmonic bio/sensor, allowing the detection of the low femtomolar concentration of analyte (LOD ~ 3 fM), thus outpassing of 4 orders of magnitude the sensitivies achieved so far on optimized nano-patterned plasmonic platforms functionalized with ultra-thin MIP layers. Thus, deformable nanoMIPs onto non-optimized plasmonic probes permit to attain ultralow detections, down to the quasi-single molecule. As a general consideration, the combination of more plasmonic transducers to different kinds of MIP receptors is discussed as a mean to attain the detection range for the selected application field.